PROFIL KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SMP NEGERI 1 SINDUE TOBATA ALAM MENYELESAIKAN SOAL MATERI GARIS DAN SUDUT DITINJAU DARI JENIS KELAMIN YANG BERKEMAMPUAN TINGGI - Faisal Faisal; Nurhayadi Nurhayadi; Rita Lefrida; Gandung Sugita (Universitas Tadulako, 2025)
This study aims to describe students’ mathematical communication skills in solving problems related to angle relationships, taking into account gender differences among students of SMP Negeri 1 Sindue Tobata. This research employed a qualitative approach with two eighth-grade students as subjects, consisting of one male and one female student, both identified as high-ability learners. Data were collected through tests and interviews. The results revealed that the male student demonstrated mathematical communication skills in understanding mathematical ideas both orally and in writing, using mathematical terms and notations, interpreting mathematical ideas through graphs and symbols, and evaluating ideas orally, although his written evaluations were still lacking. In contrast, the female student exhibited better skills in evaluating mathematical ideas both orally and in writing. These findings provide insights into the differences in mathematical communication skills between high-ability male and female students within the context of mathematics learning.